A Left-Sided Prevalence of Lentigo Maligna: A UK Based Observational Study and Review of the Evidence - Mark Gorman; Andrew Hart; Bipin Mathew (Dermatology Research and Practice)
Skin cancer has been shown to present asymmetrically, prevalent on the left side of the body, more so in subtypes of cutaneous melanoma such as lentigo maligna. Biases have been linked to cumulative UV light exposure and automobile driving patterns. Though left-right ratios have previously correlated with the side men or women tend to position themselves or countries drive on, more recent trends indicate a consistent left-sided bias. To clarify reasons for changing trends, a review of the evidence base and LM’s laterality in a UK cohort (99 cases 2000–2011) was conducted for the first time. The strong correlation of left-sided excess, found in both genders (ratios 1.381–1.5, P<0.05  X2 0.841), is congruent with more recent findings. Though evidence indicates that driving position is no longer a risk factor for LM, due most likely to improved car window UV protection, it remains the most commonly attributed cause. Understanding phenomena such as UV lights “scatter effect” or that cumulative exposure may not be a significant risk factor helps rationalize older conclusions that would otherwise appear contradictory. The reasons for left-sided excess remain unclear but may be due to factors requiring further research such as the body’s anatomical/embryological asymmetry.